Perspective: Young Workers at Higher Risk for Carcinogen Exposures - Sweet, Caitlin M.; Telfer, Joanne M.; Palmer, Alison L.; Fazel, Sajjad S.; Peters, Cheryl E. (Frontiers in Public Health, 2022)
Young workers, those under the age of 25, are considered a vulnerable working population, primarily due to their increased risk of injury. In this study we investigate if young workers may also be at an increased risk for occupational exposure to carcinogens. Using the 2006 and 2016 Canadian Census of Population and previously obtained CAREX Canada data, this study aimed to identify sectors and occupations that have high proportions of young workers and where potential exists for exposure to known and suspected carcinogens. Key groups where young workers are likely at a higher risk for occupational exposure to carcinogens were identified. Our work shows that young workers in construction, outdoor occupations, and farming are key groups that warrant further investigation. These specific groups are highlighted because of the large number of young workers employed in these sectors/situations, the high number of possible carcinogen exposures, and the potential for higher risk behavior patterns that typically occur in these types of jobs. While there is no data available to develop carcinogen exposure estimates specific to young workers, it is our perspective that young workers are likely at a higher risk for occupational exposure to carcinogens. Our findings identify opportunities to improve the occupational health and safety for this vulnerable population, particularly for young construction workers, farm workers, and outdoor workers.